An opportunity identification framework based on Topic Modeling and Sentiment Analysis for muslim-friendly hotels using textual reviews - Mulyani, Yun Prihantina; Arini, Hilya Mudrika; Dewi, Vira Laksita; Rostiani, Rokhima; Sunarharum, Tri Mulyani; Harefa, Wira Dranata; Rivadeneira , Lucía (OPSI, 2025)
Muslim-friendly hotels still lack consensus on operational standards. The operational standards have been extensively studied theoretically and empirically. However, the previous methods show some drawbacks, such as the credibility of the respondent's answers, bias, subjectivity, and small samples. Customer textual reviews have recently attracted to be utilized to capture the dynamics of customer needs. This present study introduces a framework based on topic modeling, sentiment analysis, and a modified opportunity algorithm applicable to textual data. The framework can be used to identify customer needs, and direction for product or service improvement in which competitors are taken into account. This present study utilized Tripadvisor data. Seventeen Islamic attributes have been identified from textual reviews. The framework has been applied to formulate a service improvement strategy for hotels in Moslem-dominated countries.